DOKTRIN JIHAD QITALI PERSPEKTIF SA’ĪD RAMAḌĀN AL-BŪṬI - Aminullah, Muhammad; Haqiqi, Rif'an (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2023)
The discourse on jihad, as conceptualized in Islamic law, is still often misunderstood by many groups. Their justification for jihad is often used to cast doubt on Islam's compatibility with the norms of modern international law, as stated in the UN Charter. Therefore, a true reinterpretation of Jihad is necessary to contextualize friendly Islamic law. This research is included in library research research by looking at Sa'īd Ramaḍān al-Būṭi's interpretation as a paradigm. The research stages included source collection, source classification, source analysis, and source interpretation. The results of this research can be concluded that: jihad qitāli is part of Islamic da'wah which functions as a defensive measure against enemy aggression (ḥirābah). According to Sa'īd Ramaḍān al-Būṭi, the verses of the Qur'an and hadith that came down during the Medina period cannot be interpreted as orders for offensive aggression (hujūmi). This is because the indications of attacks by the enemy were clearly visible to Rasulullah SAW. Therefore, Sa'īd Ramaḍān al-Būṭi rejected the offers of mufassirin, who interpreted the verses of the Medina period and hadiths in that period as a basis for legitimizing that kufr was the only reason for the order to fight non-Muslims.